Representasi Islam Dan Cina Dalam Hoaks Di Masa Pra Pandemi Covid-19 - Anita Sartika; Syamsul Rijal; Khaeron Sirin (STAI Bumi Silampari, 2021)
The Covid-19 pandemic is the worst pandemic in the last century, one of the factors is because the Covid-19 pandemic is accompanied by the massive spread of hoaxes related to the virus. The spread of hoaxes during the pandemic has a negative impact, including influencing public perceptions. One of the disturbing hoaxes in the pre-covid-19 pandemic was a hoax related to Islam and China. Researchers reveal how the relationship between Islam and China is represented in the Covid-19 hoax. If the relationship between Islam and China is misrepresented, it can create a wrong perception for society. This study uses an analytical model of the critical language approach of Roger Fowler et al. The results of the research, most of the hoax narratives in the pre-pandemic period represented Islam in a positive narrative, while China was represented in a negative narrative. However, the represantation of Islam and China is based on unsubstantiated claims.